Sbornaya komanda Rossii po grebnomy slalomu v 2001 godu - Slautina, I. N. (Teorija i Praktika fiziceskoj Kul'tury, 2002)
At first the development of this kind of sports is reviewed. After that the competitions of the Russian Team and some facts about the preparation are analysed. Conclusions are drawn and the perspective is shown.